ANALISIS PEMBANGUNAN PLTU TERHADAP PENCEMARAN UDARA DAN EKOSISTEM LAUT BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Putri Rizki, Haetami Lutfiah; Apriani, Rani (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2023)
This paper discusses environmental issues more precisely regarding the impact of the construction of the Batang Steam powerhouse on air pollution and marine ecosystems for future generations using qualitative juridical research methods. This paper argues that the existence of PLTU activities makes the quality of the air and sea in Batang unhealthy, which means it violates human rights to have the right to a good and healthy environment. It is hoped that the government will act decisively in supervising the activities of the Batang PLTU, so that if there is a bad impact on the environment and the community, it can provide strict sanctions. With regard to the various impacts caused, coal-fired power plants should be abandoned and switch to renewable energy sources that are more environmentally friendly.